2014
DOI: 10.1021/es501358a
|View full text |Cite
|
Sign up to set email alerts
|

Health and Air Quality Benefits of Policies to Reduce Coal-Fired Power Plant Emissions: A Case Study in North Carolina

Abstract: We analyzed sulfur dioxide (SO2) emissions and fine particulate sulfate (PM2.5 sulfate) concentrations in the southeastern United States during 2002-2012, in order to evaluate the health impacts in North Carolina (NC) of the NC Clean Smokestacks Act of 2002. This state law required progressive reductions (beyond those mandated by federal rules) in pollutant emissions from NC's coal-fired power plants. Although coal-fired power plants remain NC's leading SO2 source, a trend analysis shows significant declines i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 30 publications
1
25
0
Order By: Relevance
“…Of particular interest for the current study are the possible contributions from coal mining and coal combustion. Globally, there is an extensive body of literature that has established the air polluting effects of coal power generation . To a lesser extent, the effects of surface mining for coal on air pollution have also been reported internationally …”
mentioning
confidence: 99%
“…Of particular interest for the current study are the possible contributions from coal mining and coal combustion. Globally, there is an extensive body of literature that has established the air polluting effects of coal power generation . To a lesser extent, the effects of surface mining for coal on air pollution have also been reported internationally …”
mentioning
confidence: 99%
“…States during 2002 through 2012 [6]. Their trend analysis showed that significant declines in SO 2 (-20.3%/year) and PM 2.5 sulfate concentrations (-8.7%/year) since passage of the Clean Smokestacks Act were correlated with the risk model estimates showing decreased risk of premature death attributable to PM 2.5 sulfate in North Carolina by about 63%, resulting in an estimated 1,700 (95%CI = 1500-1800) deaths prevented in 2012.…”
Section: Trends Of Death Rates Of Emphysema Asthma and Pneumonia Inmentioning
confidence: 99%
“…Air pollution remains a critical global health and justice problem. A significant proportion of premature deaths and admissions may be avoidable by reducing air pollution (EPA, 2011;Li and Gibson, 2014;Tang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%